E-DBCM: A dynamically coupled upland and in-stream water quality model for watershed water quality simulation - Shen, Yanxia; Zhu, Zhenduo; Jiang, Chunbo (Frontiers in Water, 2022)
A dynamic bidirectional coupled modeling framework for water environment simulation (E-DBCM), including an upland watershed model (UWSM) and a two-dimensional (2D) downstream waterbody model (DWBM), is proposed. The UWSM is implemented to describe the rainfall-runoff and determine the pollutant load to downstream waterbodies, whereas the DWBM is used to simulate the pollutant transport and flood processes on downstream waterbodies. The UWSM and DWBM are spatially connected through a moving boundary, which can ensure the mass and momentum conservation. The proposed E-DBCM is verified using three case studies and the results indicate that the E-DBCM has satisfactory numerical accuracy, which can effectively reproduce the pollutant transport process and achieve satisfactory results. The water environment in Yanqi River Basin is assessed based on the proposed model. The simulated results are consistent with the measured data, indicating that the E-DBCM is reliable and the prediction accuracy can meet the requirements of engineering practices. Water is seriously polluted in this watershed, especially during peak tourist season when many pollutants are produced. Various measures should be taken to protect the water environment in this basin.